Quantitative EEG evaluation in patients with acute encephalopathy - Braga, Aline Souza Marques Da Silva; Assis, Bruno Della Ripa Rodrigues; Ribeiro, Jamil Thiago Rosa; Polla, Patricia Maria Sales; Pereira, Breno Jose Hulle; Fonseca, Ronaldo Guimarães [UNESP]; Betting, Luiz Eduardo Gomes Garcia [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 2013)
Objetivos Investigar o uso do EEG quantitativo (qEEG) em pacientes com encefalopatias agudas (EAs ) e anormalidades da atividade de base no EEG. Método s pacientes foram divididos em prognóstico favorável (grupo A, 43 pacientes) e desfavorável (grupo B, 5 pacientes). O programa EEGLAB foi utilizado para a análise do qEEG. Um gráfico da potência espectral de todos os canais foi gerado para cada participante. Os dois grupos foram comparados estatisticamente. Resultados No grupo A, a análise espectral revelou picos (frequências teta e alfa) em 84% (38/45) dos pacientes. No grupo B, um pico espectral na frequência delta foi detectado em um paciente. Os pacientes remanescentes dos dois grupos não apresentaram picos espectrais. A análise estatística mostrou menores frequências registradas nos eletrodos posteriores dos pacientes do grupo B. Conclusão O qEEG pode ser útil na avaliação de pacientes com EAs auxiliando na determinação do prognóstico.

Objective To investigate the use of quantitative EEG (qEEG) in patients with acute encephalopathies (AEs) and EEG background abnormalities. Method Patients were divided into favorable outcome (group A, 43 patients) and an unfavorable outcome (group B, 5 patients). EEGLAB software was used for the qEEG analysis. A graphic of the spectral power from all channels was generated for each participant. Statistical comparisons between the groups were performed. Results In group A, spectral analysis revealed spectral peaks (theta and alpha frequency bands) in 84% (38/45) of the patients. In group B, a spectral peak in the delta frequency range was detected in one patient. The remainder of the patients in both groups did not present spectral peaks. Statistical analysis showed lower frequencies recorded from the posterior electrodes in group B patients. Conclusion qEEG may be useful in the evaluations of patients with AEs by assisting with the prognostic determination.
Analise quantitativa do EEG em pacientes com encefalopatias agudas
Keywords: encefalopatias; coma; EEG; neurofisiologia; encephalopaties; coma; EEG; neurophysiology